A caterpillar climbing robot with spine claws and compliant structural modules. Issue 7 (15th October 2014) - Wang, Wei; Wu, Shilin
SUMMARY: This paper proposes a modular caterpillar climbing robot using spines as the attaching tools. To improve the reliability of the spines' engagement and disengagement, this paper discusses the reasonable trajectory of the spine and designs a driving mechanism of the spine based on the compliant mechanism theory. Then some compliant modules are designed and realized to build the caterpillar climbing robot. A climbing gait is designed to avoid collisions between the spines and the wall, and allows the robot to climb on a stucco-like wall with a 72○ incline. The real tests reveal that the deformation of the compliant toes reduces the sliding forces between the spines and the wall, and improve the climbing action obviously.